Pengembangan Media Pembelajaran Pop Up Book Pada Materi Simbol dan Bunyi Sila Pancasila - Alfina Zumra, Atika; Rahmi, Laili (Jayapangus Press, 2024)
The limited use of teaching media and reliance on Student Worksheets (LKS) as the sole learning tool result in monotonous teaching methods, reducing students' interest, understanding, and creativity. This study aims to identify the development process and practicality of the Pop Up Book learning media. The research method used is Research and Development (R&D) with the ADDIE development model. The data analysis techniques employed include validity and practicality analysis of the Pop Up Book learning media. The research findings indicate that the development process of the learning media comprises several stages: 1) the analysis stage shows that the use of learning media is still minimal and less effective, leading to a lack of student interest, enthusiasm, and understanding of the material. 2) the design stage involves the creation of a Pop Up Book for the symbols and sounds of the Pancasila, including media selection, material collection from various sources, and the use of Pinterest and Canva applications to organize images and initial designs. The book is made using simple materials such as HVS paper, cardboard, and glue, with techniques producing attractive three-dimensional visuals that fit the theme. 3) the development stage aims to determine the validity of the learning media. Validation results by media and material experts indicate it is highly feasible, with average scores of 94% and 92%, respectively. 4) the implementation stage aims to assess the practicality of the learning media. Responses from students and teachers show that the Pop Up Book learning media is highly practical, with an average practicality score of 90.67%. It can be concluded that the Pop Up Book learning media for the symbols and sounds of the Pancasila is proven to be highly feasible (94%) and practical (90.67%) for enhancing students' interest and understanding.